Research on the impact path of ecological civilization construction on carbon emission based on fsQCA method - Cao, Ping; Chen, Ruilin (Frontiers in Ecology and Evolution, 2023)
In order to investigate the mechanism of the effect of the construction of ecological civilization on carbon emissions. 30 provinces, cities, and autonomous regions in China were used as research objects. Based on the perspective of configuration, use the fuzzy set qualitative comparative analysis method (fsQCA), from the six dimensions of ecological civilization construction to study the configuration path of ecological civilization construction affecting carbon emissions. The findings show that the antecedent variables are related to each other and there are three types of paths to achieve low-carbon emissions, eco-economy-driven type with eco-economic construction as a key factor; eco-environmental protection type with a focus on eco-environmental protection; and land space optimization type that enhances the rational use of land resources. Comparing the low-carbon emission group pathway with the non-low-carbon emission group pathway illustrates that eco-logical management alone cannot effectively curb carbon emissions. The study explores how to promote the construction of ecological civilization and help reduce carbon emissions accordingly. To provide direction for the direction of ecological civilization construction in different regions.